The Relationship between Multiple Intelligences with Preferred Science Teaching and Science Process Skills - Mohd Ali Samsudin; Noor Hasyimah Haniza; Corrienna Abdul-Talib; Hayani Marlia Mhd Ibrahim (Journal of Education and Learning (EduLearn), 2015)
This study was undertaken to identify the relationship between multiple intelligences with preferred science teaching and science process skills. The design of the study is a survey using three questionnaires reported in the literature: Multiple Intelligences Questionnaire, Preferred Science Teaching Questionnaire and Science Process Skills Questionnaire. The study selected 300 primary school students from five (5) primary schools in Penang, Malaysia. The findings showed a relationship between kinesthetic, logical-mathematical, visual-spatial and naturalistic intelligences with the preferred science teaching. In addition there was a correlation between kinesthetic and visual-spatial intelligences with science process skills, implying that multiple intelligences are related to science learning.